Can Tax Knowledge, Tax Awareness and Socialization Increase Taxpayer Compliance? - Novita Adam; Nurjana Suleman; Maryati Kadir Thalib (Jurnal Economic Resource, 2021)
This study wants to examine how the influence of knowledge and awareness on taxpayer compliance; and want to test whether tax socialization is able to moderate to relationship awareness and taxpayer compliance. Data was collected through a questionnaire distributed to 100 taxpayers at KPP West Makassar research samples then analyzed using the Partial Least Square (PLS) approach. The results of the study found that tax knowledge and awareness affect taxpayer compliance. However, tax socialization was unable to moderate the relationship between awareness and taxpayer compliance.